Ancient Tragedy as Morphogenetic Fracture of the Modern Subject: Nietzsche and Freud in Comparison - Capodivacca, Silvia (Aesthetica Preprint, 2021)
The contribution aims to investigate how the ancient form of the theatrical representation is constituted as an aesthetic and morphological prodrome of the peculiar conception of the individual that is placed between the abyssal spread of the Dionysian on the one hand and the poisoned gift of Prometheus on the other. Reviewing some passages from the texts of Nietzsche and Freud, the thesis we intend to support is based on the assumption that the reference to the archetypal figures of ancient tragedy is not limited to outline the features of an irresolvable contradiction, or, rather, sinking into the abyss of this same statement means creating something that somehow goes beyond it. Hence the formulation of the tragic in terms of a morphogenetic fracture: an immense caesura, an appalling and non-recomposable crisis, from which nonetheless springs an army of forms of reality unparalleled in size and nature than any other generative force. The contradiction assumes in this sense the character of essentiality because it is constituted as prius, requirement and false bottom constantly present in every real morphé.